Estudo da erodibilidade de solos e rochas sedimentares de uma voçoroca na cidade de São Francisco de Assis - RS - Basso, Luciana (2013)
The study of which this Master s Thesis results was developed in a gully along State Highway RS 377, in the city of São Francisco de Assis, RS. Themain objective of this study was theerodibilityof the superficial soils(horizons A,BandC) and of the rock substrate(layers 1Aand2C) of atypical profile from the gully area. Themethodology used consisted in review ofliterature, field investigation, characterization testings, chemical testings, direct shear resistance testings, testingsforindirect valuation (degradation and infiltration testings and loss by immersion) and indirect valuation (Inderbitzen) of erodibility and the comparison with the proposal from Bastos (1999) of an estimate of erodibility of unsaturated soils in Porto Alegre region. The results obtained from the erodibility indirect testing through the erodibility factor estimate (KUSLE), from soil disaggregation potential valuation and from criterion based on MCT methodology were as follows: for horizons A, B and C and layers 2C and 1A, the values were between 0,10 and 0,21, and it was verified that these materials cannot be separated regarding erodibility. The MCT methodology presented good relation and correspondence between the testing results and the soils/rocks behavior on the studied location, proving its applicability to these materials. The direct valuation, achieved through the Inderbitzen testings, whose main purpose is to quantify the erodibility of the studied soils and rocks, through the erodibility rate, K and the hydraulic critical shearing stress (thcrít), confirmed that the loss of soil is as higher as higher is the ramp and the testing flow. According to this assessment, for sandstones samples (layers 2C and 1A), it was verified some tendency for higher values of erodibility in air-dried condition. It was also verified higher erodibility values from the horizon C and sandstone layers compared to the layer A. Regarding to the horizon B, the values were situated in an intermediate level. The horizon A presented a value for K=0,0095 g/cm²/min/Pa, lower than the result from horizon B (K=0,17 g/cm²/min/Pa). The values of K for the horizon C and the layers of sandstone were between 0,33 and 0,42 g/cm²/min/Pa. It was not possible to determine the critical hydraulic stress for the horizon A, but for the horizon B these values were between 1 and 1,3 Pa. For the horizon C and the sandstones, these values were between 0,5 and 1 Pa. The horizon C and the sandstones from the layers 2C and 1A were the more potentially erodible materials. Due to the little amount of fine portion, the little organic matter and the low plasticity, these horizons/layers are more erodible than the soils studied by Bastos (199) e Fernandes (2011). The criterion that presented a better correlation with the geothecnic purpose from Bastos (1999) were the erodibility coefficient obtained through the Inderbitzen testing and the erodibility criteria from the MCT methodology.